STRATEGI WIRAUSAHA IKAN HIAS (CUPANG) DI KELURAHAN KAMPUNG DALAM KECAMATAN SIAK SRI INDRAPURA KABUPATEN SIAK - Rima Astuti; Jaspar Jas; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Ornamental fish entrepreneurial strategy is a series of designs thatcan be taken to achieve a pre-planned plan or can be said to be a tool to createcompetitive advantage in ornamental fish marketing. The purpose of this assessment isto determine the entrepreneurial strategy of ornamental fish (hickey) in KampungDalam Village, Siak Sri Indrapura District, Siak Regency based on research indicators.They are: 1. Marketing strategy, 2. Pricing strategy, and 3. Promotion strategy. Thisstudy used a descriptive study with a one-variable naturalistic approach. Thepopulation in this study amounted to 3 people, namely ornamental fish shop owners,cashiers, and shop employees. The conclusion in the study entitled the ornamental fishentrepreneurial strategy (hickey) in Kampung Dalam Subdistrict, Siak Sri IndrapuraDistrict, Siak Regency, when viewed from the success indicators of the entrepreneurialstrategy, only 2 have been fulfilled, but it cannot be said to be a failure considering thatthis ornamental fish shop has only been running for one year and is still running.proceed. In addition, although this activity cannot be said to be successful in improvingthe economy, through this ornamental fish shop (Hickey) it has provided understandingto the community so that they can open a business to be able to help the familyeconomy.Key Words: Entrepreneurial Strategy, Ornamental Fish